USING TASK-BASED LEARNING TO TEACH ARGUMENTATIVE WRITING AND FOSTER CRITICAL THINKING IN HIGHER EDUCATION - Pohan, Erwin; Emilia, Emi; Lestari Damayanti, Ika (English Review: Journal of English Education, 2025)
This paper explores the theoretical foundations of task-based learning (TBL) and its effectiveness in enhancing argumentative writing and critical thinking skills among university students. TBL emphasizes engaging learners through meaningful tasks that mirror real-life communication, fostering linguistic competence and critical thinking—essential skills for constructing coherent and persuasive arguments. The study addresses key concepts in argumentation, such as claims, evidence, and reasoning, and underscores their significance in developing well-supported, logical arguments. Furthermore, it focuses on the exploration of (1) definition and core principles of task-based learning and its application in writing, (2) benefits of task-based learning for language and writing skills development, (3) the role of critical thinking in argumentative writing, (4) key concepts in argumentation (claims, evidence, reasoning), (5) explanation of clarity, precision, relevance, and logic (as standards of thought) in the context of argumentative writing, and (6) the relationship between critical thinking and standards of thought. This integrated framework highlights the interconnections between TBL, critical thinking, and argumentative writing and provides actionable insights for English lecturers on implementing TBL strategies in their curricula to better support students’ academic development.